Rising Through Challenges: A Phenomenological Study of Adversity Quotient in Single Mothers’ Child Stimulation Efforts - Andrian, Tedy; Iranda, Agung; Ekawati, Yun Nina; Sundjaya , Tonny; Devi, Yuli Puspita (Universitas Airlangga, 2025)
Background: Being a single mother brought various challenges, not only in the economic aspect but also in meeting the needs of early childhood development. Adversity quotients were very important for single mothers to face difficulties and devise strategies to provide the best stimulation for their children in the early stages of growth and development. Objective: This study aimed to explore the picture of the Adversity Quotient and factors that affected single mothers in an effort to achieve optimal stimulation in early childhood. This study used a phenomenological qualitative method with subjects of three single Method: mothers domiciled in Pudak Village, Kumpeh Ulu District. Data were collected through in-depth semi-structured interviews and analyzed using interpretive phenomenological analysis to understand the subjective experiences of the participants. Results: Adversity quotient in single mothers was reflected in their ability to overcome difficulties, self-control, independence, hard work, and high motivation in providing the best stimulation to their children. Factors supporting resilience included parental support, social support from the surrounding environment, religiosity, and gratitude.Conclusion: All participants showed strong dimensions of resilience and its supporting factors as they endeavored to optimally meet the needs of stimulating early childhood development despite facing various challenges as single mothers.